3D Characterization of an Intermetallic β/γ‐Titanium Aluminide Alloy1. Issue 11 (13th September 2013) - Engstler, Michael; Mayer, Svea; Pauly, Christoph; Clemens, Helmut; Mücklich, Frank
<x xml:space="preserve">Abstract</x> Intermetallic titanium aluminides have evolved into a lightweight alternative to nickel‐based superalloys because of their good mechanical properties at elevated temperatures combined with a low density. Potential fields of application include aircraft and automobile engines. Microstructure strongly influences a material's mechanical properties. Although conventional 2D image analysis provides statistically secure information about the microstructure, a complete understanding of the 3D arrangement (e.g. phase's connectivity) is not accessible. In this study, 2D image analysis, EBSD and FIB/SEM tomography are employed to analyze the 3D microstructure of a β/γ‐TiAl alloy with a nominal composition of Ti‐44Al‐7Mo‐0.1B (in at%). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>